2004
DOI: 10.1161/01.hyp.0000129825.52269.9e
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor

Abstract: Noris et al describe that preeclamptic women have decreased placental villi L-arginine concentration and overexpression of arginase II. 1 In February, Alexander et al reported that supplementing L-arginine in pregnant rats with reduced uterine perfusion decreased blood pressure, concomitantly increasing serum L-arginine levels and urinary nitrite/nitrate. 2 Both reports highlight the role of the L-arginine-nitric oxide (NO) pathway in determining normal and preeclamptic pregnancies and sustain the potential be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Rytlewski K et al [ 15 ] demonstrated a significant increase in estimated fetal body weight after the first two weeks of treatment in their L-arginine group compared to the placebo group. However, the results from other trials were different [ 27 , 28 ]. Therefore, more studies are necessary to clarify these results.…”
Section: Discussionmentioning
confidence: 91%
“…Rytlewski K et al [ 15 ] demonstrated a significant increase in estimated fetal body weight after the first two weeks of treatment in their L-arginine group compared to the placebo group. However, the results from other trials were different [ 27 , 28 ]. Therefore, more studies are necessary to clarify these results.…”
Section: Discussionmentioning
confidence: 91%
“…Some favorable effects of supplemental l -arginine on blood pressure and pregnancy outcomes were reported in patients with preeclampsia [93]. However, the data from human trials remain inconclusive.…”
Section: Placental Insufficiency and Developmental Programmingmentioning
confidence: 99%
“…( 10 , 11 ) It was already recommended that l -arginine be examined in clinical trials in high risk pregnancies ten years ago. ( 12 ) Recently, a clinical study investigated the effect of supplementations during pregnancy with l -arginine and antioxidant vitamins, and demonstrated that the intervention reduced the incidence of preeclampsia in a Mexican population at high risk of the condition. ( 13 ) With the increased need of NO to support the adaptive vasodilatation, the maternal l -arginine level has been shown to be deficient during pregnancy due to consumption by the fetus.…”
Section: Introductionmentioning
confidence: 99%